2019
DOI: 10.1186/s13104-019-4803-1
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of heart disease among adults at the Bamenda Regional Hospital, North west Cameroon: a semi urban setting

Abstract: ObjectiveWe sought to determine the spectrum of heart diseases among adult patients at the Bamenda Regional Hospital in the North West Region of Cameroon. This is a chart review of echocardiographic records.ResultsIn total, 673 records were included in our study, of which 506 had a definite heart disease. Of the 506, 93 had mixed cardiopathies. Their ages ranged from 18 to 105 years with a median age of 64.0 (Interquartile range = 47–75) years. Females accounted for a greater proportion (55.3%) of the study po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
1
3
1
Order By: Relevance
“…26 This study identified that IHD was the third leading cardiac disease etiology (17.4%). This was higher than the studies conducted in Southwest Ethiopia, 12 Nigeria, 14 North Ethiopia, 15 Southwest Cameroon, 16 Addis Ababa, Ethiopia, 20 and Northwest Cameroon, 21 in which the rates were 12%, 1.59%, 6.5%, 9.6%, 6.2%, and 7%, respectively. The variation might be attributed to differences in the study approach, time of the study, and the number of populations included between the studies.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…26 This study identified that IHD was the third leading cardiac disease etiology (17.4%). This was higher than the studies conducted in Southwest Ethiopia, 12 Nigeria, 14 North Ethiopia, 15 Southwest Cameroon, 16 Addis Ababa, Ethiopia, 20 and Northwest Cameroon, 21 in which the rates were 12%, 1.59%, 6.5%, 9.6%, 6.2%, and 7%, respectively. The variation might be attributed to differences in the study approach, time of the study, and the number of populations included between the studies.…”
Section: Discussioncontrasting
confidence: 59%
“…The finding was in line with the study conducted in Jimma, which was 12%. 29 Conversely, HHD was the second commonest type of heart disease in Southwest Ethiopia, 12 it was the first most common heart disease among the study conducted in Northwest Cameroon, 21 the rates of which were 24% and 41.1%, respectively. In support, HTN increased from 594 million in 1975 to 1.13 billion in 2015, with a high increase in low-and middle-income countries, 30 and is strongly associated with heart diseases like CHD, heart failure, AF, aortic valvular disease, left ventricular hypertrophy, and abdominal aortic aneurysms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[5,10,12] Hypertensive heart disease was the fourth commonest (13%) type of heart disease which is similar the study done in Hawassa (12.5%),but lower as compared to the nding of the previous study done at JUMC (24%) [5,14].Study from other developing countries showed HHD has become the rst leading cause of heart disease. [10,11] Hypertension was found to be the most common comorbidity associated with cardiac disease(21.3%) which similar to other studies done in Ethiopia. [9,12]…”
Section: Discussionsupporting
confidence: 86%
“…Current study Aje et al [32] Sani et al [33] Agomuoh et al [34] Adebayo et al [35] Adesagna et al [36] Akono et al [37] Number by hypertension and RHD in SSA, as reported by the THESUS-HF study. [30] Pericardial disease was found in 3.5% (N = 53) from the echocardiography done in our hospital during the mentioned period.…”
Section: Parametermentioning
confidence: 84%